Relationship between discontinuities, magnetic holes, magnetic decreases, and nonlinear Alfvén waves: Ulysses observations over the solar poles - Tsurutani, B.T.; Galvan, C.; Arballo, J.K.; Winterhalter, D.; Sakurai, R.; Smith, E.J.; Buti, B.; Lakhina, G.S.; Balogh, A. (My University, 2002)
[1] Ulysses magnetic field data are used to study magnetic field microstructure over the solar poles. Magnetic holes (MHs) and magnetic decreases (MDs) are found to be located at the phase-steepened edges of nonlinear Alfvén waves. The phase-steepened edges (directional discontinuities) occur in time-coincidence with MHs, one edge of an MD, or throughout the whole MD. These MH- and MD-related discontinuities have both rotational and compressive properties, perhaps explaining why many directional discontinuities detected in interplanetary space have non-MHD properties. The dispersive, dissipative and compressive features of nonlinear Alfvén waves may be important for the heating of the solar corona.
Keywords: Magnetic holes; Nonlinear Alfvén waves; Magnetic decreases; Solar poles; Solar corona